Maria - et forbillede for kristne? Grundtvigs syn på Jomfru Maria - Ditlevsen, Kirsten (Grundtvig-studier, 1991)
Mary - a Model for Christians..... ? Grundtvig’s View of Virgin Mary By Kirsten Ditlevsen. The Protestant Church has always tended to keep warily aloof from the Virgin Mary, and still does. After the Reformation, Mary played a very insignificant role in the church, at least up to the time of Grundtvig. The fact is that Grundtvig begins to take an interest in Mary, inspired by the church father Irenaeus. Grundtvig compares Eve in the Garden of Eden with Mary in Nazareth. Both women were met with an angel’s talk. A false angel beguiled Eve into violating the word of God; while a true angel came to Mary to announce to her that she was to give birth to the Saviour of the world. Mary immediately accepted being part of God’s plan of salvation, thus excusing Eve, her mother. In the words of Irenaeus: Mary’s virgin obedience makes up for Eve’s virgin disobedience.Inspired by Irenaeus, Grundtvig sees Mary as a guarantee of the humanity of Jesus. Jesus had a true human being as his mother, and Grundtvig describes her as an entirely ordinary mother, definitely not infallible. She is conscious that she is a humble and poor woman, whom God had granted His grace. Mary had not imagined that she should be found worthy of meeting and conversing with an angel, as it happened at the Annunciation. But nothing is impossible to God.Grundtvig makes Mary into a model for Christians because she trusts Jesus fully and firmly at the wedding in Cana; in the same manner we should trust Him so that he will help us as He helped His mother.Grundtvig also makes Mary an image of the church. Grundtvig speaks about the spiritual Virgin Mary as the mother of all Christians, i.e., the congregation. A spiritual mother is as necessary for human life as a physical mother, says Grundtvig. In the same way as the Holy Ghost overshadows the Virgin Mary, so the Holy Ghost overshadows the spiritual Virgin Mary - the congregation of the Lord.In Mary we are faced clearly with the true Christian heart. Mary believed in God with all her heart, and thus her faith is a model for how we must take in the word of God.In many of his sermons Grundtvig gives a high priority to what he sees as characteristically .female., in particular in the sermons from the 1850s. Women think with their hearts, while men think with their reason; thus women have a deeper understanding of Our Lord and His Gospel.Grundtvig advocates the idea that women too should be able to preach the Gospel, for just as it was a woman who gave birth to the Son of God, so the great Gospel about the Crucified and Resurrected was also born by a woman’s lips. And Jesus himself had the most loving relationship to women, Grundtvig says, and treated them as equals to men, so the example of Jesus must be sufficient recommendation for his servants, the clergymen. Grundtvig gives a higher priority to women and women’s experience in his sermons; thus, since half of Christendom are after all women, there is certainly reason enough to study his sermons.